2007 15th International Conference on Software, Telecommunications and Computer Networks 2007
DOI: 10.1109/softcom.2007.4446112
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of channel parameters in a multipath environment via optimizing highly oscillatory error functions using a genetic algorithm

Abstract: Channel estimation is of crucial importance for tomorrow's wireless mobile communication systems. This paper focuses on the solution of channel parameters estimation problem in a scenario involving multiple paths in the presence of additive white Gaussian noise. We assumed that number of paths in the multipath environment is known and the transmitted signal consists of attenuated and delayed replicas of a known transient signal. In order to determine the maximum likelihood estimates one has to solve a complica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…where in the relation (14), S[q k ] and R[q k ] are the timedelay samples that lie above the specified terrestrial wireless system time-delay estimation threshold.…”
Section: Terrestrial Tde Modeling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where in the relation (14), S[q k ] and R[q k ] are the timedelay samples that lie above the specified terrestrial wireless system time-delay estimation threshold.…”
Section: Terrestrial Tde Modeling and Analysismentioning
confidence: 99%
“…Multipath causes a single transmitted signal originnating from a source to arrive at a receiver via two or more different paths along with any combination of several distinct unequal length paths. These extra paths at a receiver can be synchronized with the mean scaling of the most dominant path and all the others are treated as the noise; then possible equalization strategies can be employed to improve the receiver system performance [14,15]. It is assumed that the transmitted radio signal and the number of paths in the multipath environment are known.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic algorithm (GA) [4] is the simplest EA applicable to several wireless communications problems, including joint channel and data estimation [5], user detection [6], and joint user detection and channel estimation [7], [8]. In terms of estimating wireless channel parameters, GA was used to estimate parameters in a multipath environment in [9], and has shown superior performance compared to traditional numerical methods for estimating Weibull parameters in [10]. Recent studies have also demonstrated the effectiveness of EAs in parameter estimation for α-κ-µ fading channels [11].…”
Section: Introductionmentioning
confidence: 99%
“…determination of multipaths directions of arrival (DOA). In [8], the authors resort to GA-based optimization to find the channel parameters such as multipath attenuations and delays. Recently, GA has been used to find good antenna element positions in sparse MIMO radar arrays [9] by minimizing the side-lobes of the radar pattern.…”
Section: Introductionmentioning
confidence: 99%